2020
DOI: 10.1074/jbc.ac119.011196
|View full text |Cite
|
Sign up to set email alerts
|

The cryo-EM structure of African swine fever virus unravels a unique architecture comprising two icosahedral protein capsids and two lipoprotein membranes

Abstract: African swine fever virus (ASFV) is a complex nucleocytoplasmic large DNA virus (NCLDV) that causes a devastating swine disease currently present in many countries of Africa, Europe, and Asia. Despite intense research efforts, relevant gaps in the architecture of the infectious virus particle remain. Here, we used single-particle cryo-EM to analyze the three-dimensional structure of the mature ASFV particle. Our results show that the ASFV virion, with a radial diameter of ϳ2,080 Å, encloses a genome-containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
103
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 63 publications
0
103
0
Order By: Relevance
“…The disease is caused by African swine fever virus (ASFV), a large nucleocytoplasmic virus that contains a double-stranded 170-190 kb DNA genome, encoding 151-167 open reading frames (ORFs) [1]. The ASFV virion is a complex multi-enveloped and multi icosahedral particle containing at least 68 different structural viral polypeptides and 21 cellular proteins and possess a much more complex structure than previously believed [1][2][3]. ASFV replicates predominantly in mononuclear-phagocytic cells (monocytes and macrophages), which play a front-line role in activating and orchestrating the innate and adaptive host responses.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is caused by African swine fever virus (ASFV), a large nucleocytoplasmic virus that contains a double-stranded 170-190 kb DNA genome, encoding 151-167 open reading frames (ORFs) [1]. The ASFV virion is a complex multi-enveloped and multi icosahedral particle containing at least 68 different structural viral polypeptides and 21 cellular proteins and possess a much more complex structure than previously believed [1][2][3]. ASFV replicates predominantly in mononuclear-phagocytic cells (monocytes and macrophages), which play a front-line role in activating and orchestrating the innate and adaptive host responses.…”
Section: Introductionmentioning
confidence: 99%
“…This dimension ultimately recapitulates the relative packing and angular orientation of the individual β-barrels, V1 and V2, which is reflected in the angular aperture, of helices FG1-α and FG2-α (~69° as estimated for PRD1 P3 in CHIMERA [ 23 , 51 ]) and is mainly conserved across all the PRD1-adenovirus members ( Figure 2 B and Figure 3 ; <66.9° > ±7.3° as estimated across 26 MCP structures derived either through X-ray or cryo-EM). The structural invariance of this footprint allows the identification of the double β-barrel fold even at intermediate resolution, as occurred in the case of the African Swine Fever virus (ASFV) p72 MCP whose 8280 copies compose the virion outermost capsid shell ( Figure 3 , right) [ 52 ]. The ASFV p72 double β-barrel and the MCPs of the other large nucleocytoplasmic large DNA virus (NCLDV), PBCV-1 and Faustovirus cluster together [ 26 , 33 , 53 , 54 , 55 , 56 ] ( Figure 2 B).…”
Section: Major Capsid Proteins With a Double β-Barrel Fold: The Comentioning
confidence: 99%
“…The estimated angle between the two helices FG1-α and FG2-α is ~72° in line to that found across the corresponding helices in PRD1. Right, cryo-EM map of homotrimers of ASFV MCP p72 viewed along the 3-fold axis showing the pseudo-hexameric footprint generated by the p72 protein adopting the double jelly-roll fold (EMDBid 10325); this is displayed using the local resolution and mapped onto the density (color-coded resolution bar in Å) [ 52 ].…”
Section: Figurementioning
confidence: 99%
“…In a brute-force effort to collect over 1,000 viral particles, in this issue Andrés et al (6) are able to report the structure of the complete, intact ASFV virion. Starting from the inside, the structure includes an inner nucleoid region containing the dsDNA genome (170 -190 kbp) enclosed by an inner capsid.…”
mentioning
confidence: 99%
“…Andrés et al employed additional approaches to overcome the degradation of resolution at the outer viral capsid, which contains antigenically important protein p72. To circumvent problems posed by imaging overly large particles by cryo-EM, they deconstructed the virus biochemically and then purified and resolved the structure of p72 as individual homotrimers free in solution (6). In a parallel effort, Wang et al (7) have recently reported the structure of ASFV, but they employ a different approach to resolve the outer capsid.…”
mentioning
confidence: 99%